Digital Based Mathematics Learning in Primary Education: Systematic Literatur Review - Muhaimin, Yusril Yahya; Wardani, Sri; Harianingsih, Harianingsih; Subali, Bambang; Widiati, Nuni (FKIP - Universitas Riau, 2025)
This study examines the trends and implementation of game-based learning (GBL) in primary school mathematics learning, integrating global perspectives and the Indonesian context. This study aims to: (1) identify post-2021 GBL design trends (digital vs. non-digital), (2) explore the determinants of successful implementation across different geographical contexts, and (3) analyze the synergistic role of teachers and technology in reducing the risk of disruption. A systematic literature review (SLR) following the PRISMA protocol was conducted by analyzing 15 Scopus-indexed international articles (2021-2025). Findings show that developed countries adopt more AI/AR-based digital GBL and adaptive apps, while Indonesia emphasizes hybrid approaches (culture-based board games, physical-digital integration) and affordable technologies. Key success factors include teacher-developer collaboration, technical training and cultural relevance, although challenges such as the digital divide (30% of rural schools without computers) and overly complex designs persist. Teacher-led scaffolding-based learning (pre/post-game guidance, time management) and technology-based tools (instant feedback, adaptive difficulty levels) synergistically reduced distractions, aligning with ZPD and Flow Theory principles. This study confirms the importance of glocalization - integrating global innovations with local contexts to support inclusive, adaptive and sustainable mathematics learning. The implications call for policy reforms to address infrastructure gaps, teacher capacity building and context-sensitive GBL design.